Impact of COVID-19 pandemic and diabetes on mechanical reperfusion in patients with STEMI: insights from the ISACS STEMI COVID 19 Registry - De Luca, Giuseppe; Cercek, Miha; Jensen, Lisette Okkels; Vavlukis, Marija; Calmac, Lucian; Johnson, Tom; Roura I Ferrer, Gerard; Ganyukov, Vladimir; Wojakowski, Wojtek; von Birgelen, Clemens; Versaci, Francesco; Ten Berg, Jurrien; et al. (Cardiovascular diabetology, 2020)
BACKGROUND: It has been suggested the COVID pandemic may have indirectly affected the treatment and outcome of STEMI patients, by avoidance or significant delays in contacting the emergency system. No data have been reported on the impact of diabetes on treatment and outcome of STEMI patients, that was therefore the aim of the current subanalysis conducted in patients included in the International Study on Acute Coronary Syndromes-ST Elevation Myocardial Infarction (ISACS-STEMI) COVID-19. METHODS: The ISACS-STEMI COVID-19 is a retrospective registry performed in European centers with an annual volume of > 120 primary percutaneous coronary intervention (PCI) and assessed STEMI patients, treated with primary PCI during the same periods of the years 2019 versus 2020 (March and April). Main outcomes are the incidences of primary PCI, delayed treatment, and in-hospital mortality. RESULTS: A total of 6609 patients underwent primary PCI in 77 centers, located in 18 countries. Diabetes was observed in a total of 1356 patients (20.5%), with similar proportion between 2019 and 2020. During the pandemic, there was a significant reduction in primary PCI as compared to 2019, similar in both patients with (Incidence rate ratio (IRR) 0.79 (95% CI: 0.73-0.85, p < 0.0001) and without diabetes (IRR 0.81 (95% CI: 0.78-0.85, p < 0.0001) (p int = 0.40). We observed a significant heterogeneity among centers in the population with and without diabetes (p < 0.001, respectively). The heterogeneity among centers was not related to the incidence of death due to COVID-19 in both groups of patients. Interaction was observed for Hypertension (p = 0.024) only in absence of diabetes. Furthermore, the pandemic was independently associated with a significant increase in door-to-balloon and total ischemia times only among patients without diabetes, which may have contributed to the higher mortality, during the pandemic, observed in this group of patients. CONCLUSIONS: The COVID-19 pandemic had a significant impact on the treatment of patients with STEMI, with a similar reduction in primary PCI procedures in both patients with and without diabetes. Hypertension had a significant impact on PCI reduction only among patients without diabetes. We observed a significant increase in ischemia time and door-to-balloon time mainly in absence of diabetes, that contributed to explain the increased mortality observed in this group of patients during the pandemic. TRIAL REGISTRATION NUMBER: NCT04412655.
Keywords: Registries; Humans; lidé středního věku; koronární angioplastika; Hypertension; registrace; Female; rizikové faktory; Aged; infarkt myokardu s elevacemi ST úseků; výsledek terapie; Time-to-Treatment; senioři; lidé; Europe; mortalita v nemocnicích; ST Elevation Myocardial Infarction; časové faktory; Diabetes Mellitus; COVID-19; čas zasáhnout při rozvinutí nemoci; ženské pohlaví; Male; Middle Aged; Retrospective Studies; hypertenze; Treatment Outcome; Percutaneous Coronary Intervention; retrospektivní studie; Hospital Mortality; mužské pohlaví; diabetes mellitus; Time Factors; Evropa; Risk Factors